Sources and pathways of dust during the Australian "Millennium Drought" decade. Issue 2 (19th January 2017) - O'Loingsigh, Tadhg; Chubb, Thomas; Baddock, Matthew; Kelly, Tyler; Tapper, Nigel J.; De Deckker, Patrick; McTainsh, Grant
Abstract: From the late 1990s to mid‐2010, Australia was affected by a prolonged period of drought, the "Millennium Drought, " during which numerous severe dust storms crossed the continent. We inspect this period to produce the first continental‐scale climatology of air‐parcel trajectories that is specific to dust and use it to gain new insights into dust transport dynamics over the eastern half of Australia. The analysis is based upon dust arrival times from airport meteorological observations made at nine mostly coastal cities for 2000–2009. The Hybrid Single‐Particle Lagrangian Integrated Trajectory model was used to calculate 1.26 million backward trajectories from receptor cities, with only those trajectories associated with a dust storm observation considered in the analysis of dust transport. To tie dust trajectories from receptors to likely emission sources, trajectories were linked to six known major dust source regions in and around the Lake Eyre Basin. The Lake Eyre North ephemeral lake system, alluvial‐dominated Channel Country, and agricultural Mallee‐Riverina regions emerge as important sources for the period, providing variable contributions to different parts of the seaboard as controlled by different front‐related wind systems. Our study also provides new detail regarding dust pathways from continental Australia. For the Millennium Drought we identify that the broadly established Southeast Dust Path may be more accurately subdivided into three active pathways, driven by prefrontal northerly winds and a variation in the influence of frontal westerlies. The detail of these pathways has implications for dust delivery from specific Australian sources to different marine environments. Key Points: Backward trajectories from eastern Australian observation sites produce a climatology of dust pathways explicitly linked to dust presence In linking pathways back to prominent interior source regions both the likely source of observed dust and its transport are coupled Trajectories show that existing models of continental pathways are coarse and a North East dust pathway from Australia is significant